Activation of metabotropic glutamate receptors increases cAMP accumulation in hippocampus by potentiating responses to endogenous adenosine - Winder, DG (J Neurosci, 1993)
Metabotropic glutamate receptors (mGluRs) are coupled to effector systems through GTP-binding proteins (G-proteins) and appear to mediate slow synaptic responses in the CNS. Although mGluR-mediated increases in phosphoinositide hydrolysis have been well characterized, other mechanisms for signal transduction employed by mGluRs are poorly understood. We recently reported that the selective mGluR agonist 1- aminocyclopentane-1 S,3R-dicarboxylic acid (1S,3R-ACPD) increases cAMP accumulation in rat hippocampal slices. We have now investigated the mechanisms involved in this response. A number of G-protein-linked receptors that are not directly coupled to adenylate cyclase increase cAMP accumulation by potentiating cAMP responses to other agonists. Furthermore, previous studies suggest that glutamate increases cAMP accumulation by a mechanism that is dependent upon the presence of endogenous adenosine. Therefore, we tested the hypothesis that 1S,3R- ACPD-stimulated increases in cAMP accumulation in rat hippocampal slices are dependent upon the presence of endogenous adenosine and are mediated by an mGluR that potentiates cAMP responses to other agonists. We found that adenosine deaminase abolished 1S,3R-ACPD-stimulated cAMP accumulation whereas the adenosine uptake blocker dipyridamole enhanced this response. Additionally, adenosine receptor antagonists blocked mGluR-mediated increases in cAMP accumulation with potencies that were highly correlated with their potencies at A2 adenosine receptors. Furthermore, we performed a series of studies that suggest that 1S,3R- ACPD activates an mGluR subtype that potentiates responses to agonists of other receptors that are coupled to adenylate cyclase and that 1S,3R- ACPD-stimulated increases in cAMP accumulation in hippocampal slices are mediated by potentiation of the cAMP response to low levels of endogenous adenosine that are continuously present extracellularly.